The effect of childhood sexual abuse on depressive symptoms in female college students: a serial mediation model - Zheng, Haopeng; Cai, Yan; Liu, Lei; Peng, Biao (Frontiers in Psychology, 2024)
Objective: Childhood sexual abuse (CSA) can have a negative impact on women's psychological, emotional and social functioning. The purpose of this study was to explore the relationship between CSA and depressive symptoms in female college students, as well as the mediating roles of negative core schema and experiential avoidance.Methods: 515 female college students responded to the Sexual Abuse subscale of the Childhood Trauma Questionnaire, the Depression subscale of the Depression Anxiety Stress Scale, the Brief Core Schema Scales, and the Acceptance and Action Questionnaire -II. The structural equation modelling was used for the mediation analysis.Results: There was a significant positive correlation between CSA and depressive symptoms in female college students. The theoretical model was well fitted, χ 2 /df = 3.422, RMSEA = 0.069, CFI = 0.929, TLI = 0.919. The negative core schema played a mediating role between CSA and depressive symptoms. Experiential avoidance played a mediating role between CSA and depressive symptoms. The negative core schema and experiential avoidance played a serial mediating role between CSA and depressive symptoms.These results deepen our understanding of the relationship between CSA and depressive symptoms in female college students, and provide theoretical guidance for the prevention of depression in female college students. Attention should be paid to female college students who have experienced CSA, to eliminate the adverse influence of negative core schema on these students. Meanwhile, we should teachfemale college students to accept themselves as they are, and thereby reduce their use of experiential avoidance strategies.